2021
DOI: 10.1136/bmj.n334
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 deaths in Africa: prospective systematic postmortem surveillance study

Abstract: Objective To directly measure the fatal impact of coronavirus disease 2019 (covid-19) in an urban African population. Design Prospective systematic postmortem surveillance study. Setting Zambia’s largest tertiary care referral hospital. Participants Deceased people of all ages at the University Teaching Hospital morgue in Lusaka, Zambia, enrolled within 48 hours … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
164
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(190 citation statements)
references
References 31 publications
10
164
0
Order By: Relevance
“…Nevertheless, findings from these studies taken together indicate that SARS-CoV-2 has spread widely in sub-Saharan Africa (2,3). This conclusion is supported by a postmortem study in Lusaka, Zambia, which found that among 372 deceased patients, 19.2% were PCR-positive for SARS-CoV-2 (40).…”
Section: Discussionmentioning
confidence: 83%
“…Nevertheless, findings from these studies taken together indicate that SARS-CoV-2 has spread widely in sub-Saharan Africa (2,3). This conclusion is supported by a postmortem study in Lusaka, Zambia, which found that among 372 deceased patients, 19.2% were PCR-positive for SARS-CoV-2 (40).…”
Section: Discussionmentioning
confidence: 83%
“…A seroprevalence study of anti-SARS-CoV-2 antibodies in Kenya between April and June 2020 estimated a crude national seroprevalence of 5.6%, with levels being highest in the counties of Mombasa (8.0%) and Nairobi (7.3%) [43]. A study on deceased people at the University Teaching Hospital morgue in Lusaka, Zambia, found that only 6 (9%) of 70 people, who had SARS-CoV-2 confirmed from postmortem nasopharyngeal swabs within 48 hours of death, had ever been tested before death [44]. These data suggest that there are many unreported cases and deaths due to COVID-19, a situation likely to be present in many other African countries.…”
Section: Discussionmentioning
confidence: 99%
“…It is also true that this framework integrates the evaluation of chronic disease management (eg, Hodgkin's disease; cardiovascular disease) to a greater extent than that of communicable diseases. We though that the recording of communicable diseases could be under-evaluated, especially in low-income countries due to insufficient diagnostic capacity, as it is the case with COVID-19 [ 57 ]. In the context of the emergence of chronic diseases - in low- and middle-income countries, we preferred to prioritize this measure as well.…”
Section: Discussionmentioning
confidence: 99%